Dependence of Residual CO2 of Limestones on Apparent Density. (2017) - Dolák, Dušan; Dvořák, Karel; Bureš, Jaroslav; Všijanský, Dalibor
Abstract: Important part of research of properties of limestones during firing process is knowledge of all characteristics of used samples. One of the many characteristic is the residual CO2 after firing. This parameter can be determined by various methods, however, most of them are time consuming or they need expensive instrumentation. In the evaluation of measurements of various parameters, correlation between apparent density and residual CO2 of finely ground samples was observed. This correlation was apparently linear with all measures samples. Therefore, we performed two sets of calibration firing and subsequent measurements of density and residual CO2 . Simple equation for calculation of residual CO2 and also areas of reliability were created using basic linear regression. It was shown that after initial calibration, functional correlation of these parameters with sufficient accuracy and reliability for operational use can be made.